Accumulation and distribution of micronutrients in banana cv. Williams (Musa AAA Simmonds) with different doses of nitrogen - Torres-Bazurto, Jaime; Magnitskiy, Stanislav; Sánchez, Jaiver Danilo (Sociedad Colombiana de Ciencias Hortícolas-SCCH and Universidad Pedagógica y Tecnológica de Colombia-UPTC, 2021)
This research evaluated the effect of nitrogen fertilization (0, 161, 321.8, or 483 kg ha-1) on the accumulation of Fe, Cu, Zn, Mn, and B in banana plants cv. Williams in two production cycles in Uraba, Colombia. The micronutrient accumulation models for the plants were obtained with a multivariate approach for differences between cycles, using a randomized complete block design with repeated measurements over time. The N doses with greater accumulation of Cu, Fe, Mn, Zn and B in the plants with fruits were 321.8 and 483 kg ha-1. The average sequence of micronutrient extraction by whole plants was Fe>Mn≥Zn>B>Cu in the first cycle and Fe>Cu>Mn≥Zn>B in the second cycle. The micronutrient accumulation was organ-specific and varied depending on the stage of development. Fe was the major micronutrient extracted by the corm, pseudostem, and bunch. The leaves had the greatest accumulation of Mn. The higher fertilizer doses generated a major response in terms of micronutrient extraction by the banana plants.